Task-Based Learning: A Modern Approach to TESOL on Ninth Grade Students of MTs Miftahul Midad Lumajang - Kurnia Devi Yuswandari; Yanti Ramiasih (PPPM STIT MIFTAHUL MIDAD, 2025)
This study explores the implementation of Task-Based Learning (TBL) as a modern approach to Teaching English to Speakers of Other Languages (TESOL) for ninth grade students at MTs Miftahul Midad Lumajang. The research investigates the effectiveness of TBL in enhancing students' English language proficiency, particularly in the areas of speaking, writing, reading, and listening. Using a qualitative method. The data from student surveys, interviews, classroom observations, and teacher feedback. The findings reveal that TBL significantly improved students' language skills, with particular gains in speaking fluency and writing coherence. Students showed increased motivation and engagement in the learning process, as the task oriented activities provided meaningful, real world applications of language. However, challenges such as time management, classroom organization, and unequal participation were noted. Teachers also reported the need for further professional development to effectively implement TBL strategies. Overall, this research suggests that TBL can be an effective and engaging approach to TESOL in Indonesian secondary school contexts, offering a more student centered, communicative alternative to traditional grammar focused methods. The study provides recommendations for teachers and school administrators to integrate TBL more widely in the curriculum for enhanced language learning outcomes.